Factors Influencing Dividend Policy Moderated by Market Share in Non-Financial Companies in Indonesia - Laksmitaningrum, Chintya Fadila; Joice, Sally; Muchtar, Susy (Jurnal Eksplorasi Akuntansi, 2025)
This study analyzes the effect of cost of debt, cost of equity, weighted average cost of capital (WACC), firm size, and return on assets (ROA) on dividend policy in non-financial companies listed on the Indonesia Stock Exchange for the 2022–2024 period, and examines the role of market share as a moderating variable. Dividend policy is measured using the dividend payout ratio, dividend coverage ratio, and dividend yield. The analysis method uses panel data regression with a series of statistical tests, including the Chow test, Hausman test, descriptive test, Adjusted R², F-test, and T-test. The results show that cost of debt has a significant negative effect on dividend yield, while cost of equity has a significant positive effect on dividend yield and dividend payout ratio. WACC, firm size, and ROA do not significantly influence the three dividend policy indicators. Market share is shown to have a dualistic moderating role, strengthening or weakening the relationship between internal company factors and dividend policy, depending on the indicators used. The implication of these findings is the importance of companies designing flexible dividend policies and considering the cost of capital structure and market share dynamics in making profit distribution decisions.